Monastic Buildings: A Review About New Uses on Former Monasteries. The Portuguese Cistercian Case - Martins, Ana Maria Tavares (2020)
This paper aims to present a review contribution to the history of the reform and renewal in the Portuguese Cistercian monasteries, throughout nine centuries of cultural and architectural history, but focusing on the new uses on former monasteries. The monastic Orders had a vital importance, both temporal and spatial, in the development of the urban fabric of cities. It must be considered that the transformation and development of the territory have been responsible for isolated buildings and settlements which have gradually been absorbed by the expansion of the urban fabric. The Cistercian Order played a remarkable role in the affirmation of Portugal (1143) and had an unquestionable position, since the medieval period, in the construction of a significant part of the Portuguese culture. The first Cistercian monasteries appeared in Portugal, in the 12th century, far from the urban context. Portuguese Cistercian monasteries became worthy examples of the European Cistercian architecture, although, over the time, they have been adapted, enlarged and transformed according to the styles of each epoch. The disappearance of the religious Orders, in 1834, and the successive owners adapted the monastic buildings to new uses. The monasteries have provided the contemporary city, especially from the 19th and 20th centuries, with expectant spaces or new ﬁelds of experimentation as diverse as rehabilitation, reuse, renovation and conversion. These are new spaces which adapt to new situations and new uses, thus updating themselves, so that the values of the present can be included and integrated into its history. Therefore, this paper aims to discuss, in which way the ideals and the realities of these monastic buildings and related urban spaces are divergent, but also a factor of city growth and cultural development.